GLOBAL CLIMATES OF THE VENDIAN - Chumakov N.M. (My University, 2003)
The global climate of the Vendian has been the subject of considerable debate. In view of the difficulties of stratigraphic correlations, the absence of reliably reconstructed positions of continents, the scarcity of climate indicators, and the fact that Vendian outcrop areas are widely separated, it is so far possible to identify only the most general climatic features for three Vendian time intervals. The latest Vendian (Nemakit-Daldyn) and possibly the early Tommotian age of the Lower Cambrian were characterized by a glacial climate and pronounced climatic zoning. Presumably, that time was marked by the existence of northern and southern cold climatic zones, as well as a low-latitude and partially mid-latitude warm and hot arid zone. Throughout the remaining part of the Late Vendian (Ediacaran or Redkino-Kotlin), the Earth's climate was non-glacial. The warm and hot, predominantly arid zone encompassed the low and most of middle latitudes. In the southern high latitudes, there is evidence of warm humid climate. The Early Vendian Laplandian (Varangian) time had a extremely pronounced glacial climate. Glaciations of this age have been identified almost on all large Vendian continents and on some microcontinents. According to some paleomagnetic determinations and reconstructions for continents, these glaciations covered the high, middle, and most of low latitudes, extending also into equatorial regions of the Earth. These data, however, cannot be regarded as absolutely reliable and as definitive evidence for a continuous global glaciations lasting for millions of years ("snowball Earth''). Some geological facts conflict with this hypothesis and agree better with the results of numerical simulation attesting to the presence of partially ice-free oceanic areas. This is clearly indicated by numerous glacial oscillations of different ranks. At the same time, there are as yet no compelling arguments to rule out the existence of low-latitude glaciations locally on land in the Early Vendian.
Keywords: VENDIAN; CLIMATIC ZONATION; GLACIAL AND NON-GLACIAL GLOBAL CLIMATE; GLOBAL GLACIATION; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский